Enhancing Students' English Speaking Skills through Web-Based Teaching - Irfan Suryana; Vicky Hidantikarnillah; Ikmi Nur Oktavianti (Universitas Sulawesi Barat, 2020)
Teachers play a very important role in the teaching and learning process. They should utilize effective strategies that are included in classroom management. In this digital era, the teachers should adjust their methods in delivering or explaining the materials for the students. One of the technology is the web. The aim of this study is to investigate the teacher’s perceptions of using the web to enhance students’ English speaking skills. This study was under phenomenological qualitative research and characterized by an interdisciplinary approach, especially education and technology. The direct personal interview was utilized to obtain the information from the teacher. The survey encompasses twelve questions that become different categories and was done in eight grades of class B in SMP Negeri 3 Pleret. The results showed that teaching speaking using the web can effectively enhance the students’ English speaking skills and the students give positive reactions regarding this method.